The Effect of Financial Statement Integration and Accountability Characteristics on Taxpayer Compliance Moderated by Nationalism - Sihar Tambun; Pita Rizki Handayani (Institute of Computer Science (IOCS), 2022)
The purpose of the study to prove nationalism as a moderating variable among the influence on the integration of financial statements and characteristics can be accounted for to taxpayer compliance. This type of research uses quantitative research methods. Quantitative research is research with data analyzed in the form of numbers. Quantitative descriptive research methods with the use of numbers from data collection, interpretation of data and exposure of results. This research procedure is done by conducting a questionnaire. Questionnaires are distributed using google form. The results of the study found that 1) financial statements intregation, characteristics can be accounted, and nationalism attitudes have a positive and significant effect on taxpayer compliance and 2) moderation of national attitudes on the integration of financial statements has no positive effect on taxpayer compliance while the moderation of national attitudes on characteristics can be accounted for positively on taxpayer compliance.